SISTEM AGRIBISNIS JAGUNG DI KECAMATAN ADILUWIH KABUPATEN PRINGSEWU - Virgiana, Sita; Arifin, Bustanul; Suryani, Ani (Jurnal Ilmu-Ilmu Agribisnis, 2019)
This research  aimed to know the procurement of corn production facilities, farm performance, corn marketing, supporting institutions and index of agribusiness system.  This research was conducted in Adiluwih Subdistrict of Pringsewu Regency.  The data were collected on March - April 2018 by survey method. The result of this research showed that the procurement of production facilities that did not accord to the criteria were price and quantity. The average income from the corn agribusiness system was Rp9,973,527.8/ha and it was profitable because the R/C ratio was higher than one.  Marketing of agribusiness systems was inefficient because its market was oligopsonic structure, farmers did not have the power to determine the price of corn and the profit margin ratio did not spread evenly.  The supporting institutions in Adiluwih Subdistrict were farmer groups, extension agents, financial institutions, government policies, transportation and markets.  All supporting institutions were available but not fully utilized by farmers.  The supporting institutions which related to the agribusiness system were farmer groups, government policies and extension institutions.  The agribusiness index in terms of production facilities has been good, while the agribusiness index in terms of farming and marketing performance has not been good.  In general, the corn agribusiness index has notbeen good. Key words:  agribusiness index, agribusiness system, corn